Guidelines for Setting Up a Computer Program to Aid Athletic Academic Advising - Tompkins, Shirley; Cirone, Dominic; Navins, Deborah (My University, 1985)
The article reviews computer hardware and software needs for an academic support program for athletes at a mid-major institution. It includes equipment, pricing (in 1985), and data departments might consider collecting into a database.
Keywords: technology; academic support